Effects of Thyme Extract Oils (from Thymus vulgaris, Thymus zygis, and Thymus hyemalis) on Cytokine Production and Gene Expression of oxLDL-Stimulated THP-1-Macrophages - A. Ocaña; G. Reglero (Journal of Obesity)
Properties of thyme extracts from three different species (Thymus vulgaris, Thymus zygis, and Thymus hyemalis) were examined. Two oil fractions from each species were obtained by CO2 supercritical fluid extraction. Main compounds presented in the supercritical extracts of the three thyme varieties were 1,8 cineole, thymol, camphor, borneol, and carvacrol. As a cellular model of inflammation/atherogenesis, we use human macrophages derived from THP-1 monocytes and activated by oxidized LDLs. These cells were incubated with the thyme fraction oils, and the productions and gene expressions of the inflammatory mediators TNF-α, IL-1B, IL-6, and IL-10 were determined. Thyme extracts significantly reduced production and gene expression of the proinflammatory mediators TNF-α, IL-1B, and IL-6 and highly increased these parameters on the anti-inflammatory IL-10 cytokine. Changes on production and gene expressions were dose dependent and according to the thyme content of each species. Taken together, these results may suggest that thyme extracts could have anti-inflammatory effects.